Communication and relationships: how patients perceive informational and interactional organizational justice can improve patient-centered care, a study with samples from Spain and the U.S. - Diana Pérez-Arechaederra; Elena Briones; Luis García-Ortiz (BMC Health Services Research)
Abstract Background Organizational variables as perceived organizational justice can influence patients’ behaviors. After analyzing the three tenants of patient-centered care (i.e., communication, relationships and health promotion), we identified a gap regarding how patients’ attitudes and organizational perceptions contribute to enhancing the effectiveness of patient-centered care. This study aims to improve the understanding of patients’ experiences with health care organizations to enable health care service management to enhance patient-centered care quality. Given the structural differences in healthcare systems in Spain and the U.S., we examined both contexts to strengthen our analysis of patient perceptions that are critical for improving patient-centered care across different systems. Methods We conducted a cross-sectional survey study using two data samples from Spain and the U.S. We tested the role of patients perceived interactional and informational organizational justice in health service performance with respect to patients’ behaviors of adhering to professional advice and loyalty to the service. The final sample comprised 473 health care users from Spain (male 59.2%) and 406 from the U.S. (male 52.0%), all aged 18 or older. In Spain, we developed a random sample selection from patients that visited their primary care service onsite. In the U.S., patients were invited to participate though an online survey platform that randomly selected participants from their panel database of the general population. In both samples the participants had visited a healthcare service within the past six months. We assessed perceived organizational justice (interactional and informational), adherence to professional advice, and loyalty to the service, and the mediating role of trust in healthcare providers and satisfaction with services. Results Significant correlations were found in both samples for each justice dimension with both behaviors: adherence to advise (interactional, r = 0.15/0.18, p < 0.01; informational, r = 0.19/0.19, p < 0.01) and loyalty to the service (interactional, r = 0.45/0.79, p < 0.01; informational, r = 0.45/0.70, p < 0.01). When we tested the model that included mediating patients’ attitudes of trust and satisfaction, we found that the direct relationship between informational justice and adherence still held (standardized trajectory coefficient = 0.13, p < 0.01) showing their consolidated relationship. For interactional fairness, trust and satisfaction significantly mediated the relationship with adherence. On the other hand, the relationships between both justices and patient loyalty to the service were always partially mediated by patient trust and satisfaction (model fit for interactional justice perceptions RMSEA = 0.101, CFI = 0.959, GFI = 0.959; model fit for informational justice perceptions RMSEA = 0.136, CFI = 0.937, GFI = 0.946). Conclusions Patients’ perceptions of interactional and informational justice play an essential role in their adherence to professional advice, their loyalty to the service, and their ability to develop trust and satisfaction in health services. Communication and relationship-building in patient-centered care should incorporate fairness considerations to enhance healthcare outcomes. Policies and programs should integrate these justice perceptions into patient-centered care strategies. We outline specific implications for improving healthcare quality and patient-centered care.